Dossier I: Fenómenos cadavéricos en una muestra de carne porcina - Granados Muñoz, Rolando (Quadernos de criminología, 2022)
The study of cadaveric phenomena and the development of entomology have been of interest to science. The purpose of this study is to explore these cadaveric phenomena and the entomological process, the evolution of decomposition and the presence of insects in a swine sample were recorded. Five observations were made in nine days in which descriptions and photographic captures were carried out; It is concluded that these studies may be the guideline for more elaborate research